Flood Mitigation and River Pamba in Kerala– Insights and Measures with Special Reference to Thottappally - Mounika, L; SHIVA, KUMAR VEGYARAPU (The journal of contemporary issues in business and government, 2020)
Pathanamthitta and Alleppey districts in Kerala are enriched by the cultural and historical importance of the Pamba River. The rice bowl of Kerala, Kuttanad, relies on this river to meet the state’s needs. The Pampa River caused devastation in and around Thottappally and the surrounding areas during the floods of 2018. The Thottappally spillway connects the Vembanad Lake to the Arabian Sea in a two-way exchange. The Kuttanad region and Thottappally have historically been on the receiving end of both seasonal and unseasonal rainfall. Despite this, though, Proper systems and methods must be in place in view of these considerations In addition, the ability to deal with an increase in inflows is critical. Flooding at Thottappally has caused a number of problems, and this article examines those difficulties and provides recommendations for preventing further losses.